Experiences of Hospitalization of Patients With Psychotic Disorders on Medical–Surgical Units: A Thematic Analysis. (July 2021) - Weissinger, Guy M.; Brooks Carthon, J. Margo; Ahmed, Charisse; Brawner, Bridgette M.
BACKGROUND: Individuals with psychotic disorders are more likely to have nonpsychiatric hospitalizations than the general population. Moreover, they experience worse outcomes in terms of rehospitalization, adverse events, in-hospital mortality, and longer length of stay.AIM: A patient-centered understanding of inpatient medical–surgical hospitalization experiences could shed light on disparities in hospital outcomes among individuals with psychotic disorders.METHOD: This article reports findings from Phase 1 (Qualitative) of a mixed methods, exploratory sequential study of nonpsychiatric hospitalizations of patients with psychotic disorders. Patients on medical–surgical units with diagnosed psychotic disorders ( n = 20) were interviewed about their experiences of hospitalization, and a thematic analysis was conducted of transcripts, case notes, and setting notes.RESULTS: Five themes emerged from analysis: (1) managing through hard times (subthemes: intense emotions, medically complex with many symptoms, strategies for self-management ), (2) ignored and treated unfairly, (3) actively involved in health (subthemes: seeking health education, suggesting changes ), (4) appreciation of caring providers, and (5) violence: expected and enacted . Participants connected the difficult nature of their hospitalization experiences with a variety of sources and outcomes, including strong emotions, variable relationships with providers and a struggle to receive health education.CONCLUSIONS: Nurses who care for patients with psychotic disorders in medical–surgical settings can better meet patients' needs by concentrating on relationship building, especially during initial interactions, and helping patients better manage their medical and psychiatric symptoms through both pharmaceutical and nursing interventions.